ADVANCE ATTACK AND DEFENSE STRATEGY ALGORITHM WITH DYNAMIC ROLE ASSIGNMENT FOR WHEELED SOCCER ROBOT - Rudy Dikairono; Setiawardhana Setiawardhana; Fajar Budiman; Djoko Purwanto; Tri Arief Sardjono (Universitas Trunojoyo Madura, 2021)
Game strategy is one of the most critical parts of winning a soccer robot match and cannot be separated from the cooperation among robots in making movements to score goals. In this paper, a wheeled soccer robot game strategy called advance attack and defense has been developed. The strategy is combined with dynamic role assignment, in which robot can change from an attacker to a defender and vice versa. Defender robots are not only based on defensive area but will always block opposing attacker to score goal. The attack strategy performs a rotational trajectory for attacker robot to overpass opponent robot. This strategy has been proven to increase defense and attack effectiveness. Test results using soccer robot gameplay environment simulator developed by Institut Teknologi Sepuluh Nopember Robot with Intelligent System (IRIS) team show that the advance strategies are superior compared with basic strategies. In 30 matches, the advance dynamic strategy won 80%, drew 6.7%, and obtained the highest goal difference, 85 goals. The test was then verified with the implementation in the IRIS robots and showed the same performance. The developed game algorithms were tested in 2019 Indonesian wheeled soccer robot contest (KRSBI-B) and the IRIS team won the title.